2010
DOI: 10.1016/j.ijpvp.2010.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of low-cycle fatigue of pipe elbows with local wall thinning and life estimation using finite element analysis

Abstract: Low-cycle fatigue tests were conducted using elbow specimens with local wall thinning. Local wall thinning was machined on the inside of the elbow in order to simulate metal loss from erosion corrosion. The local wall thinning was located in three different areas known as the extrados, crown and intrados. The elbow specimens were subjected to cyclic in-plane bending under displacement control without internal pressure. In addition, three-dimensional elastic-plastic analyses were also carried out using the fini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…It is concluded that elbows with thinning at the extrados have stronger resistance to low cycle fatigue failure compared to elbows with thinning at the crown and intrados. Low cycle fatigue lives predicted via FE analyses based on strain criteria correlated well with test results [17].…”
Section: Review Of Literaturesupporting
confidence: 60%
See 1 more Smart Citation
“…It is concluded that elbows with thinning at the extrados have stronger resistance to low cycle fatigue failure compared to elbows with thinning at the crown and intrados. Low cycle fatigue lives predicted via FE analyses based on strain criteria correlated well with test results [17].…”
Section: Review Of Literaturesupporting
confidence: 60%
“…Varelis et al [11] Takahashi et al [16,17] conducted experimental tests and FE analyses to investigate low cycle fatigue of thinned-wall carbon steel elbows subjected to cyclic in-plane bending in the absence of internal pressure. Thinning is located at the extrados/crown/intrados.…”
Section: Review Of Literaturementioning
confidence: 99%
“…To investigate the fracture behavior of elbow piping, many repeated load tests of elbow piping have been conducted. (Sakakida et al, 2000;Nuclear Power Engineering Corp, 2001;Otani et al, 2011;Takahashi et al, 2009;Takahashi et al, 2010).…”
Section: )mentioning
confidence: 99%
“…This work has been extended on the bending behavior of externally pressurized induction bends, used in offshore pipe applications as reported by Pappa et al [9]. Takakashi et al [10] performed in plane-bending low-cycle fatigue tests on pipe elbows specimens with local wall thinning, due to metal loss from erosion corrosion. More recently, the low-cycle fatigue of pipe elbows, subjected to severe cyclic loading, has been investigated experimentally and numerically by Varelis et al [11], [12].…”
Section: Introductionmentioning
confidence: 99%